(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2025)
This article explores the impact of educational games on the enhancement of vocabulary acquisition among English language learners. It presents a comprehensive analysis of various game-based learning strategies and their effectiveness in promoting engagement, motivation, and retention of new vocabulary. The authors review existing literature on game-based learning, highlighting the cognitive and social benefits that games offer in an educational context.